2004
DOI: 10.1158/1078-0432.ccr-03-0149
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RhoB Expression in Human Lung Cancer Progression

Abstract: Purpose: RhoB is a low molecular weight GTPase belonging to the Ras protein superfamily. Whereas most Rho proteins have been shown to have a positive role in proliferation and malignant transformation, the specific role of RhoB appears more divergent. We reported previously that RhoB inhibits cell proliferation in various human cancer cells. Here, we studied the specific role played by RhoB in human lung cancer.Experimental Design: We analyzed the expression of RhoB protein by immunostaining in human lung tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
144
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 44 publications
(43 reference statements)
12
144
1
3
Order By: Relevance
“…Fourth, we have shown that RhoB overexpression inhibits oncogenic signaling and cell proliferation in cultured human cancer cell lines and tumor growth in nude mice as well as induces apoptosis . Furthermore, we and others have recently shown that RhoB expression is suppressed during tumor progression in human head and neck, lung and brain cancer patients (Adnane et al, 2002;Mazieres et al, 2004). Finally, RhoB expression was found to be very low in 130 human cancer cell lines (Wang et al, 2003), giving further support to RhoB tumor suppressive activity.…”
Section: Discussionmentioning
confidence: 54%
“…Fourth, we have shown that RhoB overexpression inhibits oncogenic signaling and cell proliferation in cultured human cancer cell lines and tumor growth in nude mice as well as induces apoptosis . Furthermore, we and others have recently shown that RhoB expression is suppressed during tumor progression in human head and neck, lung and brain cancer patients (Adnane et al, 2002;Mazieres et al, 2004). Finally, RhoB expression was found to be very low in 130 human cancer cell lines (Wang et al, 2003), giving further support to RhoB tumor suppressive activity.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have already shown that RhoB has a pivotal role in the apoptotic response of neoplastic cells to DNA damage. 7,10,12 However, to our knowledge this study represents the first demonstration that the overexpression RhoB expression leads to in vivo tumor regression B Couderc et al of RhoB on its own using viral adenoviral transduction could induce apoptosis of cultured tumor cells.…”
Section: Discussionmentioning
confidence: 74%
“…14,29 Numerous studies have indicated a repression of GTPase RhoB in a significant number of cancers including ovarian cancer. 7,14,16 Moreover, the ability of RhoB to inhibit the tumoral growth of many cancer cell lines both in vitro and in vivo 6,7 suggests that RhoB may play a tumor suppressor role. 5 Here, we examined whether in vivo restoration of RhoB expression in RhoB downregulated ovarian cancer cells would reverse malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations